What if Alzheimer's disease could be a path to personal and social transformation - Angelica, Jade C. (2019)
Notable as the only disease among the 10 leading causes of death in the US that cannot be prevented, slowed, or cured, Alzheimer's continues to vex the most brilliant medical and scientific minds. Our national agenda seems to focus on fighting and conquering this, and seemingly every disease, perhaps in a very human effort to defeat mortality.This article offers alternative perspectives with spiritual implications by beginning with questions that ask, What if? Reflecting the intention of the biblical parables that facilitated "reversals" in thinking, the exploration of the "What ifs" could shatter our current world view and shift our attitudes about and our behavior toward persons with Alzheimer's and dementia.The journey through Alzheimer's can become a transforming experience for the millions of persons with the disease as well as the tens of millions of caregivers. It can become a spiritual journey that challenges us to accept the difficult realities of life, while inviting us to open our hearts and minds, acknowledge our interdependence, deepen our connection to ourselves, one another, and God, and believe in healing, even when cure is not possible. What if in caring for persons with Alzheimer's, we become our best selves?
Keywords: Alzheimer's Spirituality; Creative Caregiving; Improvisation; Transformation